A multicenter laboratory assessment of a new automated chemiluminescent assay for ADAMTS13 activity. (21st November 2020) - Favaloro, Emmanuel J.; Mohammed, Soma; Chapman, Kent; Swanepoel, Priscilla; Zebeljan, Diane; Sefhore, Opelo; Malan, Erica; Clifford, Joanne; Yuen, Agnes; Donikian, Dea; Kondo, Mayuko; Duncan, Elizabeth; et al.
Abstract: Background: Thrombotic thrombocytopenic purpura (TTP) is a rare but potentially fatal disorder caused by ADAMTS13 (a disintegrin and metalloproteinase with a thrombospondin type 1 motif, member 13) deficiency. Prompt identification/exclusion of TTP can thus be facilitated by rapid ADAMTS13 testing. The most commonly utilized (enzyme‐linked immunosorbent assay [ELISA]–based) assay takes several hours to perform and so does not generally permit rapid testing. Objectives: To evaluate the utility of a new automated test for ADAMTS13 activity, the HemosIL AcuStar ADAMTS13 Activity assay, based on chemiluminescence and able to be performed on an ACL AcuStar instrument within 33 minutes. Patients/Methods: This multicenter (n = 8) assessment included testing of more than 700 test samples, with similar numbers of prospective (n = 348) and retrospective (n = 385) samples. The main comparator was the Technozym ADAMTS13 Activity ELISA. We also assessed comparative performance for detection of ADAMTS13 inhibitors using a Bethesda assay. Results: Overall, the chemiluminescent assay yielded similar results to the comparator ELISA, albeit with slight negative bias. ADAMTS13 inhibitor detection was also comparable, albeit with slight positive bias with the AcuStar assay. Assay precision was similar with both assays, and we also verified assay normal reference ranges. Conclusions: The HemosIL AcuStar ADAMTS13 Activity assay provided results rapidly, which were largely comparable with the Technozym ADAMTS13 Activity ELISA assay, albeit lower on average. Conversely, inhibitor levels tended to be identified at a higher level on average. Thus, the HemosIL AcuStar ADAMTS13 Activity assay provides a fast and accurate means to quantitate plasma levels of ADAMTS13 for TTP/ADAMTS13 identification/exclusion, and potentially also for other applications.